Pengaruh Financial Literacy, Life Style Dan Income Terhadap Financial Behavior Pada Kalangan Ibu Rumah Tangga - Saputra, Dasriyan; Agnes Kurnia Tjahjono, Gabriella; Arafat, Rita (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2025)
The purpose of this study was to examine and ascertain the partial and simultaneous effects of lifestyle (X2), income (X3), and financial literacy (X1) on financial behavior (Y) among housewives in RT 16 Sepinggan Baru sub-district, Balikpapan City. A saturation sample of 159 housewives was employed in this investigation. Using the SPSS 26 software for Windows, this study included multiple linear regression, convenience sampling, purposive sampling, and questionnaire distribution. According to the study's findings, among housewives in RT 16's Sepinggan Baru subdistrict, Balikpapan, financial literacy, lifestyle, and income all significantly affect financial behavior at the same time. While lifestyle has no discernible positive or significant impact on financial behavior, financial literacy does have a partial and significant positive influence.